2009
DOI: 10.1042/bst0370387
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast catalytic processes and conformational changes in the light-driven enzyme protochlorophyllide oxidoreductase (POR)

Abstract: The enzyme POR (protochlorophyllide oxidoreductase), from the family of alcohol dehydrogenases, reduces protochlorophyllide into chlorophyllide on the absorption of light. The reduction involves the transfer of two protons and two electrons and is an important regulatory step in the biosynthesis of chlorophyll. In recent years, due to the availability of large quantities of the pure enzyme, much of the catalytic reaction has been unravelled by using a variety of spectroscopic methods, including ultrafast initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…LPOR and DPOR [23], [25], [31]), other steps of this complex pathway have only been elucidated by gene knockouts/deletions, complementation, and mutational studies [14], [32], [33]. Many of these enzymes form complexes, catalyze novel reactions and may interact with yet to be identified protein partners [34], making biochemical studies as well as heterologous pathway reconstitution particularly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…LPOR and DPOR [23], [25], [31]), other steps of this complex pathway have only been elucidated by gene knockouts/deletions, complementation, and mutational studies [14], [32], [33]. Many of these enzymes form complexes, catalyze novel reactions and may interact with yet to be identified protein partners [34], making biochemical studies as well as heterologous pathway reconstitution particularly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it was recently shown that a conformational change at the active site of the POR enzyme is necessary to activate catalysis. This first reaction step is then followed by the actual photochemical reaction, which results in the formation of a reaction intermediate (I 675 *) with rate constants of 3 and 100 ns À1 (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Light excitation of the enzyme-substrate complex induces the transfer of a hydride from the proS face of a NADPH molecule to the C-17 position of Pchlide, followed by proton donation to the C18 position by a tyrosine residue, finally leading to chlorophillide (Chlide), Scheme 12. 25,26 This reaction is an important step in the biosynthesis of chlorophyll.…”
Section: Lessons From Naturementioning
confidence: 99%